Tumor-targeted bioactive nanoprobes visualizing of hydrogen peroxide for forecasting chemotherapy-exacerbated malignant prognosis - Zhang, Fan; Jia, Yong; Chen, Fangman; Zhao, Yawei; Li, Li; Chang, Zhimin (Frontiers in Bioengineering and Biotechnology, 2023)
Fluorescent visualization of hydrogen peroxide (H2O2) in the tumor microenvironment (TME) is conducive to predicting malignant prognosis after chemotherapy. Two-photon microscopy has been employed for in vivo H2O2 detection owing to its advantages of deep penetration and low phototoxicity. In this study, a two-photon fluorescent probe (TPFP) was protected by mesoporous silica nanoparticles (MSNs) and masked by cloaking the cancer cell membranes (CM), forming a tumor-targeted bioactive nanoprobe, termed MSN@TPFP@CM. This multifunctional nanoprobe allowed for the effective and selective detection of excessive H2O2 production in chemotherapeutic Etoposide (VP-16)-challenged tumor cells using two-photon microscopy. After specific accumulation in tumors, VP-16-MSN@TPFP@CM monitored tumor-specific H2O2 levels and revealed a positive correlation between oxidative stress in the TME and chemotherapy-exacerbated malignant prognosis. Given the recent translation of fluorescent imaging into early clinical trials and the high biocompatibility of bioactive nanoprobes, our approach may pave the way for specific imaging of oxidative stress in solid tumors after treatment and provide a promising technology for malignant prognosis predictions.